2011
DOI: 10.1002/ijc.26422
|View full text |Cite
|
Sign up to set email alerts
|

Combination of plasma microRNAs with serum CA19‐9 for early detection of pancreatic cancer

Abstract: This study was performed to identify plasma microRNAs (miRNAs) as diagnostic biomarkers for pancreatic cancer (PCa) and to assess their supplementary role with serum CA19-9 in early identification of tumors. Plasma RNAs were extracted from 140 PCa patients, 111 chronic pancreatitis (CP) patients and 68 normal controls, and the relative abundances of seven miRNAs (miR-16, 21, 155, 181a, 181b, 196a and 210) were measured using real-time PCR. Their diagnostic utility for PCa and correlation with clinical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(217 citation statements)
references
References 71 publications
7
205
3
2
Order By: Relevance
“…Some studies have also combined circulating miRNA expression levels with CA 19-9 to improve diagnostic accuracy. [9,14,15] However, the diagnostic combination of miR-486-5p and miR-938 with CA 19-9 was not performed in this study.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Some studies have also combined circulating miRNA expression levels with CA 19-9 to improve diagnostic accuracy. [9,14,15] However, the diagnostic combination of miR-486-5p and miR-938 with CA 19-9 was not performed in this study.…”
Section: Resultsmentioning
confidence: 87%
“…Small nuclear U6 is less stable in fluids than in tissues, [7] whilst miR-16 is a red blood cell expressed miRNA, and variations in blood cell count and/or any hemolysis could have important implications. [19] Interestingly, highly expressed circulating miR-16 [14] and peripheral blood mononuclear cell miR-16 [15] levels have themselves been shown to discriminate PDAC from HC, and those with benign disease. Therefore, the combined use of snU6 and miR-16 might not be appropriate as endogenous control, whereas a miRNA with the least change in expression across the various samples in the array could have been chosen as a normalizer.…”
Section: Expert Commentarymentioning
confidence: 99%
“…A total of 2.5 µl synthetic C. elegans miRNA, cel-miR-39 (2x10 -3 pmol/µl synthetic RNA oligonucleotides; Qiagen, Hilden, Germany), was applied to each sample as an internal control. The method used for the identification of miR-16, miR-21, miR-103 and miR-151 in the plasma was described previously (5). The relative abundance of the miRNAs was determined using the following equation: Relative miRNA abundance = -∆∆Ct = -[(Sample Ct target -Sample Ct cell-miR-39 ) -(Control Ct target -Control Ct cell-miR-39 )].…”
Section: Quantitative Reverse Transcriptase Polymerase Chain Reactionmentioning
confidence: 99%
“…Downregulation of miR-21 results in an increased sensitivity of these cells to gemcitabine (3,(12)(13)(14). Measurement of plasma miR-21 levels and serum CA19-9 may be helpful for early detection of pancreatic cancer (5).…”
Section: A B C D E Fmentioning
confidence: 99%
“…Liu et al [34] reported a sensitivity of 88.4 % and specificity of 96.3 % in differentiating PC from CP using a combination of micro-RNA and CA 19-9.…”
Section: Detection Of Pancreatic Cancer In Chronic Pancreatitismentioning
confidence: 99%